Coaching environments and student-athletes: Perceptions of support, climate and autonomy - Noble, J.; Vermillion, M.; Foster, K. (The Sport Journal, 2016)
Understanding how athletes interact with coaches is an important topic for not only increasing performance, but also for managing developmental dynamics so often associated with coaching. As a result, the purpose of the research is to examine student-athletes` perceptions of coaching environments as related to autonomy-supportive motivational climates. Division I (formerly known as Division I AAA) student-athletes were surveyed (n=143) as part of a larger data collection process by the athletic department. Self-determination theory is applied to examine motivation, autonomy, and support, while psychosocial student development theory is used to influence variable selection relating to the student-athlete population. Statistical results indicate an overall positive perception of coaching environments by student-athletes and no differences based upon gender. Regression analyses indicate only 28% of the variance is explained by current variables/questions on athletic department survey instrument with variables of gender, type of sport played, and student classification having little to no statistically significant impact. In accordance with previous research, coaches have the ability to create a positive atmosphere and in this study student-athletes had an overall positive view of their coaches` ability to develop autonomy-supportive team climates. However, many personal-level factors could account for the large percent of variance not explained by statistical analyses in the current study.